History of islam (the age of the rightly-guided caliphs al-khulafa ar-rashiddun) uthman ibn affan (1st caliphs) - Abdul aziz maulvi (Dar-us-Salam, 2012)
Abu Bakr as-Siddiq (c. 573-634 CE) was the first caliph, or successor to the Prophet Muhammad, marking the beginning of the Rashidun Caliphate. He ruled from 632 to 634 CE, a period following the Prophet's death and characterized by consolidating Islam's foundations and suppressing rebellions after his death. His reign saw the unification of the Arabian Peninsula under Islamic rule and the start of expansion beyond Arabia.